Mapeamento estratégico dos materiais utilizados no encapsulamento de semicondutores - Cerqueira, Marnio Lucio Soares (Universidade do Vale do Rio dos Sinos, 2015)
In 2013, Brazil was the second largest consumer of electronic equipment in the world. During that period, expenses with electronics in Brazil exceeded those of economic powers such as Japan, Germany, Russia and the United States. On top of the list of imported products for the electronic industry in 2013 were the following products: components for telecommunications, semiconductors and components for the IT industry. Regarding semiconductors, Brazil imported 4.5 billion dollars in 2012 and almost 5 billion dollars in 2014, resulting in a 10% increase in the trade balance deficit. In order to try to minimize the trade balance deficit and encourage the development of the semiconductor production chain, the Brazilian government has adopted a State policy to encourage the development of this industry by establishing the Program for the Support of Technology Development in the Semiconductor Industry (PADIS). This program, which was established in 2007, was designed to provide tax incentives and thus create investment alternatives. Today, in Brazil, semiconductor packaging is made by two companies, but 100% of the raw materials are imported. A future hurdle and, therefore, one of the areas that should be analyzed in order to increase productivity is the development of new materials for the manufacturing of packaged electronic products. This study conducted a mapping of the materials used to package BGA (Ball Grid Array) semiconductors. These materials are divided into direct materials (that are part of the structure of the packaged product) and indirect materials (that aid the packaging process). The goal of the research was to map and identify the direct materials used in the BGA semiconductor packaging industry so that this information could lay the foundation for the development of materials that could be procured from supplying sources other than the currently existing chain. The method used in this research was based on the prioritization matrix and we were able to establish a priority ranking for the direct materials used in semiconductor packaging.
Keywords: Encapsulamento; Semicondutores; Materiais; Mapeamento; Packaging; Semiconductors; Materials; Mapping; ACCNPQ::Engenharias::Engenharia Elétrica